Bewegungskulturen im Wandel: Der Sport der Medialen Moderne – Gesellschaftstheoretische Verortungen - Mittag, Jürgen; Nieland, Jörg-Uwe; Schürmann, Volker; Stibbe, Günter; Haut, Jan (transcript, 2016)
Sport is changing unmistakably. Classic club sport with regular training times in spaces that are devoted to sport are becoming less attractive. Sport activities which are characterized by individual motivation, time and place (such as jogging or skateboarding), are enjoying a continual increase in numbers. How is sporting activity presently taking form in comparison to the classical Olympism of modernity? The contributors investigate how processes of change in the cultures of sport and movement can be socio-theoretically outlined, and show the extent to which they have a seismographic function for societal processes.